Genetic dissection of maize regeneration and wheat disease resistance - Lin, Guifang (Kansas State University, 2021)
The growing human population worldwide and the changing growth environments require significant crop improvement, which can be accelerated by plant genome engineering. Developing plant cultivars amenable to transformation and improving understanding of the genetic bases of important phenotypic traits can facilitate the use of advanced genome engineering technologies. This dissertation is focused on the genetic analysis of maize transformation and wheat resistance to the disease of leaf rust. The results will provide knowledge to improve crop transformation and wheat disease resistance. Plant transformation is a powerful tool for crop improvement and gene function validation. However, the transformation efficiency of maize is highly dependent on the tissue types and the genotypes. The maize inbred line A188 is amenable to transformation. A188 also exhibits many contrasting traits to the inbred line B73, which is recalcitrant to transformation. B73 was used to generate the first maize reference genome. The lack of genome sequences of A188 limits the use of A188 as a model for functional studies. Here, a chromosome-level genome assembly of A188 was constructed using long reads and optical physical maps. Genome comparison of A188 with B73 based on both whole genome alignments and sequencing read depths identified approximately 1.1 Gb syntenic sequences as well as extensive structural variation. Further, transcriptome and epigenome analyses with the A188 reference genome revealed enhanced gene expression of defense pathways and altered DNA methylation patterns of embryonic callus. The A188 genome assembly provides a foundational resource for analyses of genome variation and gene function in maize. In maize, morphologic types of calli induced from immature embryos are associated with the regeneration capability, which is a major factor determining the transformation efficiency. Here, two contrasting callus types, slow-growth type I calli and fast-growth type II calli, from the selected B73xA188 F2 population were sequenced using Genotyping-By-Sequencing (GBS) and RNA-Seq. With both approaches, the genomic loci associated with the callus type were mapped to chromosomes 2, 5, 6, 8, and 9. From F2 RNA-Seq, differentially expressed genes were identified from the comparison of type II and I calli. In addition, RNA-Seq analysis was performed using fast- and slow-growth calli identified for the A188 calli. Gene ontology (GO) enrichment analysis showed that the down-regulated genes in type II F2 calli and fast-growth A188 calli, as respectively compared to type I calli and slow-growth A188 calli, are overrepresented in the pathway related to cell wall organization, suggesting the role of cell wall formation in the callus development. Besides maize genetic and genomic studies, the dissertation includes the cloning of a leaf rust resistance gene in wheat. Wheat leaf rust disease is caused by a fungal pathogen, Puccinia triticina. The Lr42 gene from the wheat wild relative Aegilops tauschii confers resistance to all leaf rust races tested to date. Through bulked segregant RNA-Seq (BSR-Seq) mapping and further fine mapping, we identified an Lr42 candidate gene, which encodes a nucleotide-binding site leucine-rich repeat (NLR) protein. Transformation of the candidate gene to a leaf rust-susceptible wheat cultivar markedly enhanced the disease resistance, confirming the candidate NLR gene is the Lr42 gene. Cloning of Lr42 expands the repertoire of cloned rust resistance genes, as well as provides precise diagnostic gene markers for wheat improvement.
Keywords: Maize regeneration; Callus; Genome assembly; Structural variation; Leaf rust; Lr42